A review on anti-cancer properties of quercetin in gastric cancer - Xie, Xiaoxia; Wei, Yan (Frontiers in Pharmacology, 2025)
This review paper focuses on the multifaceted roles and therapeutic potential of quercetin in gastric cancer (GC). Quercetin, a natural flavonoid compound abundant in dietary sources such as nuts, teas, vegetables, and herbs, has garnered significant attention due to its anticancer properties. Accumulated evidence demonstrates quercetin’s inhibitory effects against GC by targeting key pathways such as cell cycle regulation, fatty acid synthesis, and mitochondrial apoptosis, thereby exerting anti-proliferative and apoptotic strategies. Furthermore, quercetin effectively alleviates GC-related inflammation, optimizing the tumor microenvironment. Mechanistically, quercetin induces various forms of programmed cell death in GC cells, including ferroptosis, pyroptosis, and autophagy, through regulating specific molecular targets. Additionally, quercetin inhibits GC angiogenesis by downregulating vascular endothelial growth factor A (VEGF-A) and its receptor VEGFR-2 expression, and demonstrates anti-metastatic effects by modulating urokinase-type plasminogen activator (uPA) and its receptor (uPAR) function. As research delves deeper into the mechanisms of quercetin’s actions and its validation in clinical trials, its prospects as a novel therapeutic agent for GC become increasingly promising. Quercetin’s low toxicity and ability to synergize with other anticancer drugs make it a potential key component in comprehensive GC treatment strategies, significantly enhancing patient prognosis and quality of life.